PENTINGKAH ISLAMIC SOCIAL REPORTING BAGI ISLAMIC CORPORATE GOVERNANCE DAN MANAJEMEN LABA? - Septiani, Nurul Rizky; Rahayu, Sri; Ridwan, Muhammad (Imanensi: Jurnal Ekonomi, Manajemen, dan Akuntansi Islam, 2023)
The purpose of this study is to find out how Islamic Corporate Governance affects earnings management through Islamic Social Reporting. This study used path analysis and Sobel's test on 14 sample banks selected using purposive sampling. Based on the results of the study it was found that Islamic Corporate Governance influences earnings management practices and Islamic Social Reporting. Islamic Social Reporting is unable to mediate the relationship between Islamic Corporate Governance and earnings management. In Indonesia, the use of ISR reporting is still voluntary for sharia entities, this has resulted in several index items not being fulfilled so that they have not had a significant effect on management, especially in earnings management practices. Abstrak Tujuan dari penelitian ini adalah untuk mengetahui bagaimana Islamic Corporate Governance mempengaruhi manajemen laba melalui Islamic Social Reporting. Penelitian ini menggunakan analisis jalur dan uji Sobel pada 14 bank sampel yang dipilih menggunakan purposive sampling. Berdasarkan hasil penelitian ditemukan bahwa Islamic Corporate Governance berpengaruh terhadap praktik manajemen laba dan Islamic Social Reporting. Islamic Social Reporting tidak mampu memediasi hubungan antara Islamic Corporate Governancedan manajemen laba. Di Indonesia, penggunaan pelaporan ISR masil bersifat sukarela bagi entitas syariah, hal ini menyebabkan beberapa item indeks tidak terpenuhi sehingga belum memberikan pengaruh yang signifikan terhadap manajemen khususnya dalam praktik manajemen laba.